Spatial variability and influence of biological parameters on microplastic ingestion by Boops boops (L.) along the Italian coasts (Western Mediterranean Sea). (August 2020) - Sbrana, Alice; Valente, Tommaso; Scacco, Umberto; Bianchi, Jessica; Silvestri, Cecilia; Palazzo, Luca; de Lucia, Giuseppe Andrea; Valerani, Claudio; Ardizzone, Giandomenico; Matiddi, Marco
Abstract: Recently, many studies focus on the ingestion of microplastics by marine biota. Fish exploit almost every kind of marine environment, occupy many ecological niches and are an important food source for human populations worldwide. For these reasons, they seem to represent very appropriate biological indicators of microplastic ingestion. UNEP/MAP SPA/RAC (2018) identified the bogue, Boops boops (Linnaeus, 1758), as a possible target species for monitoring microplastic ingestion in fish populations. This study provides the first report of microplastic ingestion by B. boops from the Tyrrhenian and the Ligurian Seas (Western Mediterranean Sea). Generalized Linear Mixed Models were used to analyse the relationship among biological parameters and environmental factors. A total of 379 bogues were collected in three Italian regions, subject to different anthropogenic pressures (river input, human population, shipping lanes and distance from the coast). Microplastics were detected in the gastrointestinal tract of most individuals (56%) with a mean of 1.8 (±0.2) microplastics per individual. Our study further confirms that this species is able to highlight differences in the ingestion of microplastics according to local anthropization, resulting Latium region to be the most polluted. Fish with lower physical condition are more likely to ingest microplastics, suggesting a relationship with the level of local environmental contamination. Finally, the ingestion of microplastics might be influenced by behavioural differences between sexes. According to our results, males ingest significantly more microplastics than females (p < 0.05). Our research confirms that an extensive knowledge on the biology of a bioindicator species is a priority for developing a valid monitoring strategy, such as the Marine Strategy Framework Directive for European waters. Graphical abstract: Image 1 Highlights: First report on microplastic ingestion by B. boops from the Italian coasts. Coastal pressures explain the differences found in microplastic ingestion. Fish with lower physical condition are more likely to ingest microplastics. Sexual differences in the ingestion of microplastics by B. boops. Abstract : Coastal pressures and fish condition factor explain the differences found in microplastic ingestion by Boops boops (Linnaeus, 1758) along the Italian coasts (Western Mediterranean Sea).